Preface to the 3rd International Uniportal VATS Course-Berlin Special Issue - Ismail, Mahmoud; Gonzalez-Rivas, Diego (Journal of Thoracic Disease, 2017)
The International Uniportal VATS Course is a three-day-masterclass symposium jointly organized by the University Hospital Charité in Berlin (Germany), the University Hospital in Coruña (Spain), and the Shanghai Pulmonary Hospital, Tongji University, Shanghai (China). This symposium addresses the techniques and advances in uniportal VATS by lectures, discussions and video sessions on the first day and Live Surgery of major pulmonary resections via uniportal VATS on the second day. The third day is a Hands-on class (Wetlab) for a limited group.